The diagnosis of scientific reasoning skills: how teachers’ professional knowledge predicts their diagnostic accuracy - Amadeus J. Pickal; Katharina Engelmann; Clark A. Chinn; Birgit J. Neuhaus; Raimund Girwidz; Christof Wecker (Frontiers in Education, 2023)
Diagnostic competences of teachers are an essential prerequisite for the individual support of students and, therefore, highly important. There is a substantial amount of research on teachers’ diagnostic competences, mostly operationalized as diagnostic accuracy, and on how diagnostic competences may be influenced by teachers’ professional knowledge base. While this line of research already includes studies on the influence of teachers’ content knowledge (CK), pedagogical content knowledge (PCK), and pedagogical-psychological knowledge (PK) on the diagnosis of subject-specific knowledge or skills, research on the diagnosis of cross-domain skills (i.e., skills relevant for more than one subject), such as scientific reasoning, is lacking although students’ scientific reasoning skills are regarded as important for multiple school subjects (e.g., biology or physics). This study investigates how the accuracy of pre-service teachers’ diagnosis of scientific reasoning is influenced by teachers’ own scientific reasoning skills (one kind of CK), their topic-specific knowledge (i.e., knowledge about a topic that constitutes the thematic background for teaching scientific reasoning; which is another kind of CK), and their knowledge about the diagnosis of scientific reasoning (one kind of PCK) and whether the relationships between professional knowledge and diagnostic accuracy are similar across subjects. The design of the study was correlational. The participants completed several tests for the kinds of professional knowledge mentioned and questionnaires for several control variables. To ensure sufficient variation in pre-service teachers’ PCK, half of the participants additionally read a text about the diagnosis of scientific reasoning. Afterwards, the participants completed one of two parallel video-based simulations (depicting a biology or physics lesson) measuring diagnostic accuracy. The pre-service teachers’ own scientific reasoning skills (CK) were a statistically significant predictor of diagnostic accuracy, whereas topic-specific knowledge (CK) or knowledge about the diagnosis of scientific reasoning (PCK), as manipulated by the text, were not. Additionally, no statistically significant interactions between subject (biology or physics) and the different kinds of professional knowledge were found. These findings emphasize that not all facets of professional knowledge seem to be equally important for the diagnosis of scientific reasoning skills, but more research is needed to clarify the generality of these findings.